2007
DOI: 10.1016/j.febslet.2007.04.078
|View full text |Cite
|
Sign up to set email alerts
|

Osteosarcoma cell‐calcium signaling through tissue factor–factor VIIa complex and factor Xa

Abstract: The cells responsible for bone formation express protease-activated receptors. Although serine protease thrombin has been shown to elicit functional responses in bone cells that impact on cell survival and alkaline phosphatase activity, nothing is known about tissue factor, factor VIIa, and factor Xa, the serine proteases that act upstream of thrombin in the coagulation cascade. This paper demonstrates that tissue factor is expressed in the osteoblast-like cell line SaOS-2 and, that tissue factor in a factor V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Moreover, it has been shown that FXainduced PAR-1 activation enhances nuclear factor KB activity, as well as expression of angiogenesis-promoting gene, Cyr6l, and connective tissue growth factor (CTGF) in Hela cells (Riewald et al, 2001). Similarly, FXa-induced PAR-1 and -2 activation enhances cell viability by a sustained calcium signaling in human osteosarcoma cells (Daubie et al, 2007). Furthermore, Morris et al (2006) demonstrated that PAR-2 is essential for FXa-induced signaling, migration and invasion of breast cancer cells.…”
Section: Effect Of Fxa In Cancer Pathologymentioning
confidence: 99%
“…Moreover, it has been shown that FXainduced PAR-1 activation enhances nuclear factor KB activity, as well as expression of angiogenesis-promoting gene, Cyr6l, and connective tissue growth factor (CTGF) in Hela cells (Riewald et al, 2001). Similarly, FXa-induced PAR-1 and -2 activation enhances cell viability by a sustained calcium signaling in human osteosarcoma cells (Daubie et al, 2007). Furthermore, Morris et al (2006) demonstrated that PAR-2 is essential for FXa-induced signaling, migration and invasion of breast cancer cells.…”
Section: Effect Of Fxa In Cancer Pathologymentioning
confidence: 99%
“…However, PAR 2 is now known to be activated by the Tissue Factor/VIIa binary complex and by Factor Xa, which can cleave PAR 2 either independently, or with greater efficiency as part of a ternary complex with TF and VIIa ( Camerer et al , 2000 ; Riewald et al , 2001 ). PAR 2 activation by coagulation proteases is now known to initiate a number of important signalling events, including signalling and migration of cancer cells ( Morris et al , 2006 ), induction of angiogenesis ( Belting et al , 2004 ; Uusitalo‐Jarvinen et al , 2007 ) and signalling in Osteosarcoma cells ( Daubie et al , 2007 ).…”
Section: Searching For the Proteinases Responsible For Par Activationmentioning
confidence: 99%
“…In another study, the OS cell line SAOS-2 was shown to express TF, and the TF:FVIIa complex on these cells induced calcium signaling through PAR-2. (19)…”
Section: Introductionmentioning
confidence: 99%